(untitled) (Iranian Journal of Kidney Diseases, 2014)
Sagliker syndrome was introduced in 2004 in patients with end-stage renal disease and severe secondary hyperparathyroidism. This syndrome describes maxillary and mandibular deformities, dental abnormalities, benign soft tissue tumors in mouth, and various kinds of skeletal changes including short stature and fingertip abnormalities. There are a few reports from different regions of the world. The aim of this study is to report 5 cases of the Sagliker syndrome from Iran.